Thermal and rheological effects of sepiolite in linear low‐density polyethylene/starch blend. Issue 2 (23rd May 2012) - Mir, Sadullah; Yasin, Tariq; Halley, Peter J.; Siddiqi, Humaira Masood; Ozdemir, Orhan; Nguyen, Anh
Abstract Effect of different concentrations of sepiolite on thermal and rheological properties of linear low‐density polyethylene/starch blend was investigated. Vinyl trimethoxy silane was used as compatibilizing and crosslinking agent. The composites were produced by peroxide‐initiated melt mixing technique. Improved thermal stability and tensile strength were observed in crosslinked formulations. Maximum tensile properties were observed in composites containing 2 parts per hundred (phr) sepiolite and 15 phr starch. Rheological study of crosslinked composite showed a linear viscoelastic behavior with high complex viscosity and dynamic shear storage modulus. Scanning electron microscopy also revealed that silane has improved the dispersion of filler and interaction among the polymer and filler interphase. These results suggest that the presence of sepiolite act as an effective filler to enhance the thermal and rheological properties. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci, 2013